Family farming and distribution of agricultural products: the experience of the sudam branch (Itacoatiara-AM) - e Lima, Emilly Felipe de Lima; Alves, Rute Holanda Lopes; Oliveira, Elizângela de Jesus; Rocha, Alice Nascimento Teixeira; Coelho, Moises Israel Belchior de Andrade (Brazilian Journal of Production Engineering, 2020)
The economic reality of Brazilian families has always been a problem for the country. For this reason, some families are looking for alternative forms of family support, one of the available options is to use agriculture as a source of income and a means of survival. Most of these families live in rural areas and have their own land suitable for farming, as well as specific natural resources, making family farming an accessible activity. This research aims to study the process of disposal of agricultural production from SUDAM’s branch to the Rural Producer Fair located in Itacoatiara-AM, analyzing the forms of transportation and the distribution chain between the farmer and the marketer. The methodology for this study is divided into two phases: the first is the visit to the study location, to identify elements relevant to the research and search for changes that occurred during the established time, and in the second one, data were collected about the means of transport used, storage of the products and analysis of the parameters of the physical distribution of the products.